RELEVANSI DISKUSI KELOMPOK UNTUK MENINGKATKAN KEMAMPUAN GURU AGAMA HINDU DALAM MENYAJIKAN PEMBELAJARAN INOVATIF - I Made Arka (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2018)
Technological advances provide many offers and options for the education to support the learning process so that the learning processes become more effective and efficient for the learners. The group discussion among classroom teachers in the form of KKG to discuss the problem of utilizing the school environment as a source of learning to be relevant is applied. The focus of this study is the improvement of the ability of the teachers in presenting innovative learning through the use of school environment as a source of learning through the discussion of teacher work group in the Elementary School Cluster I Blahbatuh District Gianyar Regency year lesson 2014/2015. Based on the results of the research, there is relevance to the improvement of the teachers’ ability in presenting innovative learning with the utilization of school environment as a learning resource through teacher work group discussion approach in Blahbatuh District at the Elementary School Cluster, Gianyar Regency lesson year 2014/2015.